2014
DOI: 10.3906/sag-1209-72
|View full text |Cite
|
Sign up to set email alerts
|

Detection of cagA and vacA genotypes of Helicobacter pylori isolates from a university hospital in Ankara region, Turkey

Abstract: The cagA and vacA profiles and their association with clinical findings show a distinct geographical distribution. In the present study, we aimed to determine the cagA status and vacA allelic subtypes in strains isolated from a university hospital in Ankara and to evaluate their associations with histopathological and endoscopic findings. Materials and methods:A total of 120 H. pylori strains from stock cultures positive for the ureA gene were randomly included in the present study. Of these strains, cagA and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 34 publications
2
3
2
Order By: Relevance
“…The s1b subtypes are rare in other regions and less virulent than other s1 subtypes [36,37]. The strains in the present study belong to western type, as studies indicated s1b subtype is rarely found in East-Asian countries [29,32,38]. Our results revealed m2 as the main allele that similar to studies from Iraq, Turkey, Iran, Saudi Arabia, and the middle east region characterized m2 as the main allele [14,32,33,[39][40][41][42].…”
Section: Resultssupporting
confidence: 87%
See 4 more Smart Citations
“…The s1b subtypes are rare in other regions and less virulent than other s1 subtypes [36,37]. The strains in the present study belong to western type, as studies indicated s1b subtype is rarely found in East-Asian countries [29,32,38]. Our results revealed m2 as the main allele that similar to studies from Iraq, Turkey, Iran, Saudi Arabia, and the middle east region characterized m2 as the main allele [14,32,33,[39][40][41][42].…”
Section: Resultssupporting
confidence: 87%
“…However, the presence vacA gene within these isolates was increasing the pathogenicity and it had a statistically positive correlation with the disease (p=0.01 at a level 0.05). In comparison with the other studies that performed in the middle east region like Turkey and Egypt, which found vacAs1a allele is dominant (70.1% and 72.5%, respectively) than vacAs1b allele (2.8% and 7.2%, respectively) and 27.1% and 21.7%, respectively, as vacA s2 [32,33]. The allelotype s1a is more active than s1b [29], and with other vacA genotypes, the combination is associated with greater pathogenicity and virulence related to gastric cancer and peptic ulceration [34,35].…”
Section: Resultscontrasting
confidence: 60%
See 3 more Smart Citations